The Competitiveness of Indonesian Halal Food Exports in Global Market Competition Industry - Masruroh, Nikmatul (Economica: Jurnal Ekonomi Islam, 2020)
Abstract:Â Indonesia's position in the global competition for the halal food industry is not yet at the top competitive position. However, there is a significant change in the position of the competitiveness. The change can be seen from the Global Islamic Economy Indicator report for 2020/2021, which positions Indonesia at number 4 (fourth) in the halal food industry. Previously, Indonesia had never been in the top 10 positions. Since Indonesia is the first country ranked in halal consumption, the new ranking position is an achievement. The high competitiveness position during the COVID-19 pandemic also becomes an obstacle to make Indonesia a World Halal Center in 2024. This study aims to discuss an in-depth analysis of the implementation of halal value chain policies in Indonesia and the impact of implementing these policies on the export competitiveness of the Indonesian halal food industry. This study used a qualitative approach with a phenomenological type through data collection by interviewing export business actors in the halal food industry. The experiences of some informants are the key to answers the objectives of this study. This research produces the first halal value chain policy stated in the Halal Product Guarantee Law No. 33 of 2014, which requires all food entrepreneurs to carry out halal certification. The halal value chain in Indonesia applies the principle of traceability which makes Indonesian halal food products competitive. The second application of the principle of traceability is different from other countries, making halal food products produced by Indonesia acceptable to importing countries, especially OIC countries.Abstrak:Â Posisi Indonesia dalam persaingan global industri makanan halal belum berada pada posisi kompetitif teratas. Namun, ada perubahan signifikan dalam posisi daya saing. Perubahan tersebut terlihat dari laporan Global Islamic Economy Indicator 2020/2021 yang menempatkan Indonesia pada peringkat 4 (empat) dalam industri makanan halal. Sebelumnya, Indonesia belum pernah berada di posisi 10 besar. Karena Indonesia adalah negara pertama yang menempati peringkat pertama dalam konsumsi halal, posisi peringkat baru tersebut merupakan sebuah pencapaian. Posisi daya saing yang tinggi di masa pandemi COVID-19 juga menjadi kendala untuk menjadikan Indonesia sebagai World Halal Center pada tahun 2024. kebijakan daya saing ekspor industri makanan halal Indonesia. Penelitian ini menggunakan pendekatan kualitatif dengan tipe fenomenologis melalui pengumpulan data dengan mewawancarai pelaku usaha ekspor pada industri makanan halal. Pengalaman beberapa informan menjadi kunci untuk menjawab tujuan penelitian ini. Penelitian ini menghasilkan kebijakan rantai nilai halal pertama yang tertuang dalam Undang-Undang Jaminan Produk Halal Nomor 33 Tahun 2014, yang mewajibkan semua pengusaha makanan untuk melakukan sertifikasi halal. Rantai nilai halal di Indonesia menerapkan prinsip ketertelusuran yang membuat produk makanan halal Indonesia berdaya saing. Penerapan kedua prinsip ketertelusuran berbeda dengan negara lain, menjadikan produk pangan halal produksi Indonesia dapat diterima oleh negara pengimpor khususnya negara OKI.